Bacterial neuraminidase rescues influenza virus replication from inhibition by a neuraminidase inhibitor. - Tomoko Nishikawa; Kazufumi Shimizu; Torahiko Tanaka; Kazumichi Kuroda; Tadatoshi Takayama; Tatsuo Yamamoto; Nobuhiro Hanada; Yoshiki Hamada (PLoS ONE, 2012)
Influenza virus neuraminidase (NA) cleaves terminal sialic acid residues on oligosaccharide chains that are receptors for virus binding, thus playing an important role in the release of virions from infected cells to promote the spread of cell-to-cell infection. In addition, NA plays a role at the initial stage of viral infection in the respiratory tract by degrading hemagglutination inhibitors in body fluid which competitively inhibit receptor binding of the virus. Current first line anti-influenza drugs are viral NA-specific inhibitors, which do not inhibit bacterial neuraminidases. Since neuraminidase producing bacteria have been isolated from oral and upper respiratory commensal bacterial flora, we posited that bacterial neuraminidases could decrease the antiviral effectiveness of NA inhibitor drugs in respiratory organs when viral NA is inhibited. Using in vitro models of infection, we aimed to clarify the effects of bacterial neuraminidases on influenza virus infection in the presence of the NA inhibitor drug zanamivir. We found that zanamivir reduced progeny virus yield to less than 2% of that in its absence, however the yield was restored almost entirely by the exogenous addition of bacterial neuraminidase from Streptococcus pneumoniae. Furthermore, cell-to-cell infection was severely inhibited by zanamivir but restored by the addition of bacterial neuraminidase. Next we examined the effects of bacterial neuraminidase on hemagglutination inhibition and infectivity neutralization activities of human saliva in the presence of zanamivir. We found that the drug enhanced both inhibitory activities of saliva, while the addition of bacterial neuraminidase diminished this enhancement. Altogether, our results showed that bacterial neuraminidases functioned as the predominant NA when viral NA was inhibited to promote the spread of infection and to inactivate the neutralization activity of saliva. We propose that neuraminidase from bacterial flora in patients may reduce the efficacy of NA inhibitor drugs during influenza virus infection. (295 words).